Respuesta :

Answer:

- 2(x - 6)(x - 4)

Step-by-step explanation:

Given

- 2x² + 20x - 48 ← factor out - 2 from each term

= - 2 (x² - 10x + 24) ← factor the quadratic

Consider the factors of the constant term (+ 24) which sum to give the coefficient of the x- term (- 10)

The factors are - 6 and - 4, since

- 6 × - 4 = + 24 and - 6 - 4 = - 10, thus

x² - 10x + 24 = (x - 6)x - 4) and

- 2x² + 20x - 48 = - 2 (x - 6)(x - 4) ← in factored form

2x(-X+12)—4(x-12) where the roots/answers are 4 and 6
ACCESS MORE